If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(r-4)=3(r-4)
We simplify the equation to the form, which is simple to understand
7(r-4)=3(r-4)
Reorder the terms in parentheses
+(+7r-28)=3*(r-4)
Remove unnecessary parentheses
+7r-28=+3+*(+r-4+)
Reorder the terms in parentheses
+7r-28=+(+3r-12)
Remove unnecessary parentheses
+7r-28=+3r-12
We move all terms containing r to the left and all other terms to the right.
+7r-3r=-12+28
We simplify left and right side of the equation.
+4r=+16
We divide both sides of the equation by 4 to get r.
r=4
| s^2=-14-9s | | -12+3x=x-6 | | 3-5[5-(6y-5)]= | | 2(b-7)=4(b-5) | | 16-44=6(x-1)-4 | | d=h-64 | | 7*ex=14 | | 22w=15 | | 5(8m+8)=-6(8+8m) | | 3p(p+5)=0 | | 1-3m=1-7m | | 7ex=14 | | 2(x-4)+3x=12 | | 7x-(2x-4)=19 | | 7(4x+6)=-6(1-6x) | | 12.5y=225 | | 6(5p+8)=4(4+8p) | | x^2+13+42= | | 13+8x=x+6 | | 3x^2+30x=72 | | 15x^5-2x^3=24 | | 7x+1=-11+4x | | -x=0.75 | | B(t)=10et | | 11+8x=10x-3 | | -3(1+4p)=69 | | 3x(a-2b)+3b= | | -124=-2p+4(2-5p) | | 8a+3=6a+2 | | -124=2p+4(2-5p) | | 20=5b+8-b | | 2b+7b=9 |